Pengaruh Komponen 4A Terhadap Minat Kunjung Ulang Wisatawan Pada Destinasi Wisata Bayt Al-Qur’an Al-Akbar Kota Palembang - Alfitriani Alfitriani; Welly Andrika Putri; Ummasyroh Ummasyroh (Jurnal Aplikasi Manajemen dan Bisnis, 2021)
The purpose of the research is to identify the effect of the tourism 4A components is tourist attraction, acsssibilities, amenities and ancillary service at the Bayt Al-Qur’an Al-Akbar tourist destination in the city of Palembang. This research used a quantitative descriptive approach. This research used descriptive analysis and multiple linear regression analysis.. The sampling technique used in this research is non probability sampling with incidental sampling approach. The sample in this research were the visitors of Bayt Al-Qur’an Al-Akbar tourist destination in Palembang city with 100 respondents. Based on the T test results, it has known that tourist attractions and aminities have positive and significant effect towards interest to revisit in Bayt Al-Qur’an Al-Akbar, while accesibilities and ancillary service have no significant effect on the tourists' revisiting interest. Based on research result that tourist attraction has the most dominant influence on the interest in revisiting tourist. The better a tourist attraction have, the bigger tourists' revisiting interest will be at Bayt Al-Qur’an Al-Akbar Palembang.